ADVANCED POWER SUPPLY SYSTEM OF APPROACH LIGHTS AT CIVIL AVIATION AERODROMES - Дев'яткіна, Світлана; Молчанова, Катерина; Яремич, Тетяна; Сірий, Дмитро (SWorldJournal, 2024)
Modern airfield light systems belong to the class of complex topological systems, which have the direct influence on flight safety level at the of visual piloting stage. The general technical requirements of international and national standards regardin